2009
DOI: 10.1007/s11084-009-9177-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Mirror Symmetry Breaking in the Aldol Reaction and its Potential Relevance in Prebiotic Chemistry

Abstract: The origin of the single chirality of most biomolecules is still a great puzzle. Carbohydrates could form in the formose reaction, which is proposed to be autocatalytic and contains aldol reaction steps. Based on our earlier observation of organoautocatalysis and spontaneous enantioenrichment in absence of deliberate chiral influences in the aldol reaction of acetone and p-nitrobenzaldehyde we suggest that a similar effect might be present also in the aldol reactions involved in gluconeogenesis. Herein we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 41 publications
1
56
1
2
Order By: Relevance
“…Therefore, for SMSB at the formation of condensation polymers, homochiral mutualistic reaction networks are the possible reaction networks; Viedma-like for condensation polymers [48] and then hypercyclic at the replicator level, after the emergence of other catalytic functionalities [27]. Frank-like networks would be reasonable only during the early stages of chemical evolution, for example in amino acid synthesis, based on Strecker-like processes [56], or in sugar synthesis, based on the autocatalytic formose reaction [68]. However, the large ee values obtained in these initial SMSBs must be expected to survive after being rather strongly diminished at the decisive stages of biopolymer formation.…”
Section: Type Of Reaction Networkmentioning
confidence: 99%
“…Therefore, for SMSB at the formation of condensation polymers, homochiral mutualistic reaction networks are the possible reaction networks; Viedma-like for condensation polymers [48] and then hypercyclic at the replicator level, after the emergence of other catalytic functionalities [27]. Frank-like networks would be reasonable only during the early stages of chemical evolution, for example in amino acid synthesis, based on Strecker-like processes [56], or in sugar synthesis, based on the autocatalytic formose reaction [68]. However, the large ee values obtained in these initial SMSBs must be expected to survive after being rather strongly diminished at the decisive stages of biopolymer formation.…”
Section: Type Of Reaction Networkmentioning
confidence: 99%
“…The first example of asymmetric autocatalysis for an organocatalytic (metal-free) system was reported by Mauksch and Tsogoeva in 2007 for the reversible Mannich reaction of acetone and N-PMP-protected α-imino ethyl glyoxylate ( Figure 5) [29], followed by demonstration of spontaneous asymmetric amplification under nominally achiral starting conditions for the same reactive system and by the same authors [30,31].…”
Section: Reviewmentioning
confidence: 77%
“…This mechanism, extended to account for the chirality of the template [31], provides a simple explanation for the observed chiral induction in the organoautocatalytic Mannich reaction: selective transition state structures (where the chiral product template catalyzes formation of new product molecules of the same absolute configuration) may yield homochiral dimers, while antiselective transition state structures (where the product template catalyzes formation of new product with opposite absolute configuration) may yield heterochiral dimers. For the Mannich reaction, the formation of homochiral dimers in the autocatalytic step was indeed 67% yield [20] 35% ee found to be kinetically preferred, in accord with the observed enantioselectivity [29].…”
Section: Reviewmentioning
confidence: 99%
“…The connection of amino acid handedness and those of sugars has also been recently established by Nanita and Cooks [55]. Very recently, it was also suggested that asymmetric autocatalysis in the aldol reaction might play a role in gluconeogenesis via the formose reaction [56].…”
Section: Autocatalysis and Self-replication 833mentioning
confidence: 79%
“…Such a reaction scheme, which involves subsequent dissociation of the dimer product to release the monomeric catalytic template molecules [58], appears more plausible in organo-autocatalytic reactions [52,56] than schemes that require the regeneration of the catalyst or those that give only monomeric initial product. However, the mechanism is not nonlinear and therefore cannot give asymmetric amplification, because the ratio of formation rates of the enantiomers is proportional to the ratio of their concentrations:…”
Section: Autocatalysis and Self-replicationmentioning
confidence: 99%